The Vietnamese population of Megophrys kuatunensis (Amphibia: Megophryidae) represents a new species of Asian horned frog from Vietnam and southern China - Tapley, Benjamin; Cutajar, Timothy; Mahony, Stephen; Nguyen, Chung Thanh; Dau, Vinh Quang; Nguyen, Tao Thien; Luong, Hao Van; Rowley, Jodi J. L. (Zootaxa, 2017)
The Asian frog genus Megophrys is a diverse group of morphologically conserved, forest-dwelling frogs. The genus harbours highly localised species diversification and new species continue to be described on a regular basis. We examined the taxonomic status of a population of Megophrys frogs from the Hoang Lien Range in northern Vietnam and southern China previously identified as M. kuatunensis (subgenus Panophrys). Preliminary phylogenetic analyses using a fragment of 16S rDNA places the species in question within the Megophrys (subgenus Panophrys) species group, a primarily Chinese radiation within the genus. On the basis of morphological, molecular and bioacoustic data, we conclude that this population does not represent M. kuatunensis, or any known species in the genus. We herein describe this species of Megophrys as new. Known only from Sa Pa District, Lao Cai Province in Vietnam and Jinping County, Yunnan Province in China, the new species is likely to be threatened by ongoing deforestation in the region. We provide an updated species description of M. kuatunensis based on type specimens, and suggest that M. kuatunensis is likely to be restricted to eastern China.